Two somali half‐siblings with CHST3‐related chondrodysplasia illustrating the phenotypic spectrum and intrafamilial variability. Issue 10 (5th August 2013) - Tanteles, George A; Dixit, Abhijit; Dhar, Sunil; Suri, Mohnish
ABSTRACT Deficiency of carbohydrate sulfotransferase 3 (CHST3; also known as chondroitin‐6‐sulfotranferase) has been associated with a phenotype of severe chondrodysplasia and progressive spinal involvement. Recent reports indicate that affected individuals initially present with neonatal multiple joint dislocations. We describe a 14‐year‐old Somali patient and her 3‐year‐old maternal half‐brother with novel homozygous CHST3 mutations. The proband presented at the age 5½ years with short stature and genua valga. Her clinical course was characterized by rapid progression of spinal deformities and large joint contractures. Her half‐brother presented at birth with bilateral knee dislocation and talipes equinovarus. This report of a Somali family with CHST3‐related chondrodysplasia illustrates the intrafamilial variability in phenotypic expression of this rare disorder. © 2013 Wiley Periodicals, Inc.